Biopsychosocial Factors Affecting the Quality of Life of Hemodialysis Patients - Anggraini, Merry Tiyas; Gunadi, Gunadi (Jurnal Promosi Kesehatan Indonesia, 2023)
Background: Hemodialysis is performed to support the life of Chronic Kidney Disease patients. However, it affects the patient's quality of life in some cases. Clinical factors get enough attention in daily medical practice, while patients' psychological and social aspects are often ignored. This study aims to analyze the biopsychosocial factors affecting hemodialysis patients' quality of life at Roemani Hospital Semarang.Method: This is descriptive-analytic research with a cross-sectional approach. Samples were hemodialysis patients at Roemani Hospital, Semarang, with a total number of samples was 80 people. The data taken are primary data derived from questionnaire interviews and results of laboratory investigations. Data analysis used the chi-square test and the Spearman test.Results: Statistical test results obtained for the variable gender p = 0.358, education p= 0.462, employment p = 0.239, comorbid diseases p = 0.347, length of time undergoing hemodialysis p = 0.024, psychological function p = 0.280, family supports p=0.526, age r = 0.001 and p = – 0.992, hemoglobin r = 0.129 and p = 0.254, urea r = -0.089 and p = 0.432, creatinine r = 0.022 and p = 0.844. Based on these results, there was no relationship between age, gender, educational level, employment, comorbid disease, psychological functioning, family supports, hemoglobin, urea, and creatinine levels, and there was a significant relationship between the length of time undergoing hemodialysis and the quality of life of hemodialysis patients at Roemani Hospital Semarang.